Signature of Plausible Accreting Supermassive Black Holes in Mrk 261/262 and Mrk 266 - Gagik Ter-Kazarian; Lusine Sargsyan (Advances in Astronomy)
We address the neutrino radiation of plausible accreting supermassive black holes closely linking to the 5 nuclear components of galaxy samples of Mrk 261/262 and Mrk 266. We predict a time delay before neutrino emission of the same scale as the age of the Universe. The ultrahigh energy neutrinos are produced in superdense protomatter medium via simple (quark or pionic reactions) or modified URCA processes (G. Gamow was inspired to name the process URCA after the name of a casino in Rio de Janeiro). The resulting neutrino fluxes for quark reactions are ranging from to , where is the opening parameter. For pionic and modified URCA reactions, the fluxes are and , respectively. These fluxes are highly beamed along the plane of accretion disk, peaked at ultrahigh energies, and collimated in smaller opening angle .